Evolution of the hemiascomycete yeasts: on life styles and the importance of inbreeding - Knop, Michael (Bioessays, 2006)
The term ‘breeding system’ is used to describe the morphological and behavioural aspects of the sexual life cycle of a species. The yeast breeding system provides three alternatives that enable hapoids to return to the diploid state that is necessary for meiosis: mating of unrelated haploids (amphimixis), mating between spores from the same tetrad (intratetrad mating, automixis) and mother daughter mating upon mating type switching (haplo-selfing). The frequency of specific mating events affects the level of heterozygosity present in individuals and the genetic diversity of populations. This review discuses the reproductive strategies of yeasts, in particular S. cerevisiae (Bakers' or budding yeast). Emphasis is put on intratetrad mating, its implication for diversity, and how the particular genome structure could have evolved to ensure the preservation of a high degree of heterozygosity in conjunction with frequent intratetrad matings. I also discuss how the ability of yeast to control the number of spores that are formed accounts for high intratetrad mating rates and for enhanced transmission of genomic variation. I extend the discussion to natural genetic variation and propose that a high level of plasticity is inherent in the yeast breeding system, which may allow variation of the breeding behaviour in accordance with the needs imposed by the environment. BioEssays 28: 696-708, 2006. © 2006 Wiley Periodicals, Inc.
Gesehen am 16.08.2017